Breaking Free: The Genomics of Allopolyploidy-Facilitated Niche Expansion in White Clover. Issue 7 (25th April 2019) - Griffiths, Andrew G.; Moraga, Roger; Tausen, Marni; Gupta, Vikas; Bilton, Timothy P.; Campbell, Matthew A.; Ashby, Rachael; Nagy, Istvan; Khan, Anar; Larking, Anna; Anderson, Craig; Franzmayr, Benjamin; et al.
Abstract : Allopolyploid white clover arose in the last glaciation, retained progenitor genome integrity, and the few genes switching between homoeologues across tissues were enriched for flavonoid synthesis. Abstract: The merging of distinct genomes, allopolyploidization, is a widespread phenomenon in plants. It generates adaptive potential through increased genetic diversity, but examples demonstrating its exploitation remain scarce. White clover ( Trifolium repens ) is a ubiquitous temperate allotetraploid forage crop derived from two European diploid progenitors confined to extreme coastal or alpine habitats. We sequenced and assembled the genomes and transcriptomes of this species complex to gain insight into the genesis of white clover and the consequences of allopolyploidization. Based on these data, we estimate that white clover originated ∼15, 000 to 28, 000 years ago during the last glaciation when alpine and coastal progenitors were likely colocated in glacial refugia. We found evidence of progenitor diversity carryover through multiple hybridization events and show that the progenitor subgenomes have retained integrity and gene expression activity as they traveled within white clover from their original confined habitats to a global presence. At the transcriptional level, we observed remarkably stable subgenome expression ratios across tissues. Among the few genes that show tissue-specific switching between homeologous gene copies, we found flavonoid biosynthesis genes strongly overrepresented, suggesting an adaptive role of some allopolyploidy-associated transcriptional changes. Our results highlight white clover as an example of allopolyploidy-facilitated niche expansion, where two progenitor genomes, adapted and confined to disparate and highly specialized habitats, expanded to a ubiquitous global presence after glaciation-associated allopolyploidization.